Optimization of Guidance and Supervision of Governance in Garut Region: Challenges and Strategies - Hamzah, Nabiel Waluya; Maygaza Anhara Putra Brata; Bintang Khoirul Akbar; Pangeran Dirgantara; Ivan Darmawan (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Optimizing the development and supervision of governance in the Garut Region is a strategic effort to improve the effectiveness, transparency, and accountability of governance. This study identifies the main challenges faced, namely limited resources, regulatory complexity, and corrupt and nepotistic practices. In facing these challenges, several strategies are implemented, including strengthening human resource capacity through continuous training, utilizing information technology to improve efficiency and transparency, increasing community participation through online feedback and complaint platforms, and closer cooperation with external supervisory institutions. The implementation of these strategies requires careful planning, adequate resource allocation, effective monitoring and evaluation, and strong political commitment and support. Thus, governance in the Garut Region is expected to run more optimally, provide better public services, and improve community welfare